Determinants of Halal Business Practices in Muslim Minority Countries: Evidence from Finland - Husaeni, Uus Ahmad; Ayoob, Mohammed Ashfaq (Indonesian Journal of Halal Research, 2024)
Halal business practices are developing in majority-Muslim countries and within companies in Muslim minority countries such as Finland. It consistently shows an interest in developing the halal industry, as evidenced by the development of companies that practice halal business in these countries. This study examines the factors influencing halal company practices while offering halal goods or services in Finland, a nation with a large Muslim population. The surveys were given online and offline to Finnish businesses that have achieved halal certification as a data collection strategy. PLS-SEM, or partial least square-structural equation modeling, was used to analyze data from 32 replies. This study found that halal values and the spirit of innovation encourage Finnish companies to enter the halal business. In addition, companies' halal business practices in Finland are strongly influenced by the interaction between internal and external driving factors. Businesses in nations where Muslims make up the minority can be encouraged to engage in halal commerce in several ways. Individuals who are aware of halal's advantages, are drawn to innovation, are under external pressure to conduct halal business and have internal circumstances that allow them to view the halal business phenomena as a chance to advance their nation's commercial interests.